A compact dual band MIMO/diversity antenna for WLAN applications - Singh H.S.; Pandey G.K.; Bharti P.K.; Meshram M.K. (My University, 2025)
A compact dual-band MIMO/diversity antenna is presented with J-slot suitable for 2.45/5.80 GHz WLAN applications in handheld devices. The radiating elements are two planar inverted F antennas (PIFA) constructed by metallic plates and parasitic elements. The antenna is designed to operate at the resonant frequency 2.45GHz and 5.8GHz of WLAN bands. The proposed antenna having excellent Envelope Correlation Coefficient (ECC) is well below 0.01, which meet the diversity performances of MIMO (multiple-input multiple-output) antenna. The proposed MIMO antenna is characterized with S-parameters, surface current distributions, diversity parameters, and radiation patterns. © 2013 IEEE.